Stress investigation on a cracked craze interacting with a nearby circular inclusion in polymer composites - Zhang, Yan Mei (2017)
In polymer composites, inclusions (fillers) are introduced into the glassy polymeric matrices in order to improve the toughness properties as the brittleness is one of the fatal drawbacks for glassy polymers. For the first time, in our current study, the stress analysis has been performed on the interaction between a circular inclusion and a craze with an internal small crack in polymeric composites. A craze can be treated as a crack with fibrils bridging the two crack surfaces. The forces applied by the fibrils to the crack surfaces (pulling the two surfaces closer) depend on the crack opening displacement. However, the crack opening displacement is directly related to the forces applied by the craze fibrils. To solve this dilemma, an iterative procedure is proposed for the first time to solve the formulated singular integral equations. The craze thickness profiles, the cohesive stress distribution, and the fracture toughness of the polymeric composites are investigated thoroughly. Moreover, due to the influence of the inclusion, the uneven craze thickness profiles are observed from the left to the right part of the entire craze zone.